Chromatographic Techniques and Pharmacological Analysis as a Quality Control Strategy for Serjania triquetra a Traditional Medicinal Plant - A. Berenice Aguilar-Guadarrama; Guadalupe Yáñez-Ibarra; Martha Edith Cancino-Marentes; Paola González-Ibarra; Rolffy Ortiz-Andrade; Amanda Sánchez-Recillas; Javier-German Rod; Yoshajandith Aguirre-Vidal; Irma-Martha; Gabriela Ávila-Villarreal (MDPI AG, 2022)
Serjania triquetra is a medicinal plant widely used in traditional medicine for the treatment of urinary tract diseases, renal affections, and its complications. The population can buy this plant in folk markets as a raw material mixed with several herbal remedies or as a health supplement. On the market, two commercial presentations were found for the vegetal material; one had a bulk appearance and the other was marketed wrapped in cellophane bags (HESt-2, HESt-3). Nevertheless, the plant has not been exhaustively investigated and quality control techniques have not been developed. This research aimed to realize a phytochemical study using an authentic, freshly collected sample as a reference for S. triquetra (HESt-1), using the compounds identified. A method for the determination of preliminary chromatographic fingerprinting was developed. Additionally, the vasorelaxant effect from three samples was evaluated with ex vivo rat models. Thus, three hydroalcoholic extracts (HESt-1, HESt-2, and HESt-3) were prepared by maceration. A total of nine compounds were fully identified from HESt-1 after the extract was subjected to open-column chromatography. Seven metabolites were detected by gas chromatography, while ursolic acid (UA) and allantoin were isolated and identified using UPLC-MS and NMR, respectively. Three extracts were analyzed for their chromatographic fingerprint by UPLC-MS. Biological activity was explored by ex vivo rat aorta ring model to evaluate vasorelaxant activity. All extracts showed a vasorelaxant effect in a concentration-dependent and endothelium-dependent manner. S. triquetra vascular activity may be attributed to UA and allantoin compounds previously described in the literature for this activity.